16th International Congress of Metrology 2013
DOI: 10.1051/metrology/201316002
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of uncertainty to the homogeneity study in the certification of a candidate certified reference material in fish matrix

Abstract: Abstract.A homogeneity study in the preparation of a fish candidate certified reference material is reported. In the present study, homogeneity was examined by flow injection analysis cold vapour atomic absorption spectrometry technique (FIA-CV-AAS). Total mercury and methylmercury were studied in this study. Univariate analysis of variance (ANOVA) was performed for all analytes. The results were evaluated using an F-test, which demonstrated no significant difference for the between-bottle results. It is indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, the PT samples were found homogenous. F test indicated that the result of the homogeneity is insignificant if F < Fcrit, with the critical value of F for α =5 %, and e gives the level for which the observed F = Fcrit [19].…”
Section: Homogeneity Testingmentioning
confidence: 99%
“…Therefore, the PT samples were found homogenous. F test indicated that the result of the homogeneity is insignificant if F < Fcrit, with the critical value of F for α =5 %, and e gives the level for which the observed F = Fcrit [19].…”
Section: Homogeneity Testingmentioning
confidence: 99%